An Analysis of M31 and its Satellite Galaxies Using RR Lyrae Variables. Issue Volume 14:Issue S344(2019) (August 2018) - Tanakul, Nahathai; Sarajedini, Ata
Abstract: RR Lyrae stars are powerful tools to study their host populations. Information such as distance, metallicity, reddening, and age can be obtained from their pulsation properties. Dwarf spheroidal (dSph) galaxies are the most common type of galaxy in the Local Group. They are found around massive hosts such as the Milky Way (MW) and M31 and are suggested to be the present-day counterparts to systems from which spheroids and stellar halos of larger galaxies were assembled. By comparing RR Lyraes in these dSphs with their host galaxies, we hope to understand more about the formation of these galaxies. In order to achieve this goal, we have analyzed six fields in M31 using archival imaging from the Hubble Space Telescope. Published data for M31, M33, and several M31 dSphs are also included. The results are then compared with those in the MW to better constrain the early history of these systems.